Research on Warehouse Target Locating and Tracking Based on EKF and UKF - Bian Guangrong; Kong Fancheng; Zhang Honghai; Cao Jinrong; Shi Hongyan (Institute of Advanced Engineering and Science, 2014)
The paper firstly established the warehouse target locating and tracking system model based on wireless sensor networks. The principle of Location and tracking is applying maximum likelihood estimation algorithm of multilateral measurement method to calculating the coordinates of the unknown node. According to monitoring motion trajectory of the same unknown target node within a continuous period of time, the motion equation can be established. When the state equation of warehouse target tracking system is non-linear, EKF and UKF filtering algorithm are respectively applied to acquiring the state estimate of the warehouse target motion equation, so as to achieve the effective tracking of warehouse target. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5063